Communication Technologies in Smart Grid - Miladinovic, Nikola M.; Polužanski, Vladimir S.; Milosavljević, Srđan B. (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
The role of communication technologies in Smart Grid is crucial. It is necessary to provide a link between all parts of the network, but also to meet performance related to bandwidth, delay and package loss. This paper provides an overview of the technologies, currently in use, that are not in compliance with the Smart Grid concept and technologies that are in line with the Smart Grid concept. Considering that the Smart Grid is open to the flow of information in all directions, it is necessary to provide cyber security for advanced networks.